Implementasi Surat Keputusan Walikota Banjarmasin Nomor 238 Tahun 2023 Tentang Penetapan Nilai Jual Objek Pajak Khusus Bumi Sebagai Dasar Pengenaan Pajak Bumi dan Bangunan di Kota Banjarmasin - Luthfiya Safitri; Budi Suryadi (Universitas Warmadewa, 2025)
This study aims to evaluate the implementation of Banjarmasin Mayoral Decree Number 238 of 2023 concerning the Determination of the Sales Value of Special Taxable Land Objects as the Basis for Imposing Land and Building Tax (PBB) in Banjarmasin City, and to identify factors hindering its implementation. The background to this study is the recent adjustment of the NJOP (Value-Based Property Tax) seven years after the last adjustment, resulting in a significant spike in PBB bills and public objections. This policy was also not accompanied by adequate public awareness by the government. This study used a descriptive qualitative approach, with data collection techniques including in-depth interviews, field observations, and documentation. The analysis was conducted using George Edward III's theory of policy implementation (communication, resources, disposition, and bureaucratic structure) and Mazmanian and Sabatier's theory (socio-political environmental factors). The results indicate that the policy's implementation has not been optimal. Obstacles occurred in all aspects of implementation according to Edward III: ineffective communication, limited human resources and data, less than fully supportive attitudes of implementers, and an uncoordinated bureaucratic structure. Socio-political environmental factors also hamper implementation, such as a lack of public support, low public participation, and post-pandemic economic conditions that make it difficult for the public to accept tax increases. This study recommends the need for transparency, improved communication, updated taxpayer data, and increased public participation in the implementation of PBB policies.